(untitled) (Salam International Academic Journal, 2022)
As a universal religion, Islam looks at the issues of international relations from a different perspective in comparison to other approaches in the field of international relations. Islam considers the field of international relations as a way to maintaining stability and international security in line with the integration of the international community; a concept that you can observe in Islam’s emphasis on the unity of Islamic societies. What is important from the point of view of Islam is not to maintain the current ongoing situation based on security policies in accordance with common and internationally accepted strategies, but in accordance with a normative-rule-based approach and based on the road map to the advancement of entire mankind. This research aims to study the position and importance of Islam’s liberating approach (which prevent problems from arising) to political phenomena and concepts, instead of their superficial and problem-solving view in a dialectical concept. The importance of this research can be stated in the point that Islam has its own unique theory about international relations, which is the best solutions to get rid of problems in international relations in any situation. This research answers the question that; Does Islam as a universal and comprehensive religion, have any solutions for international relations? The type of research in this article is analytical-descriptive.